Determination of the Product Mix and the Business Policy of an Insurance Company—A Portfolio Approach - Kahane, Yehuda (Management Science, 1977)
This paper sets out a model which simultaneously determines the optimal composition of the insurance and investment portfolios of an insurance company using Sharpe's Single-Index Technique. This technique can be explained for management as follows: different product lines that a multi-product firm offers have different rates of return and different risks associated with those rates of return. Taking into account both risks and rates of return, what is the best mix of product lines for a firm to offer in the marketplace? This approach is especially suitable for insurance because of data limitations. This type of analysis can make a useful contribution in shaping the firm's product mix and marketing policy.